Isolasi dan Karakterisasi Cendawan Pathogen Daun Jagung Manis (Zea mays) Varietas Talenta menggunakan Metode Direct Plating Dan Moist Chamber di BBPP Ketindan, Jawa Timur - nurul fadilah; Yuni Sri Rahayu; Lutfi Tri Andriani (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
Market demanding for corn increases with the years. The greatest request of all types of maize is the sweet corn (Zea mays) talenta variety. However, domestic productions arenot sufficient for this corn. This is due to problems such as corn disease which drastically derailed yields. This disease comes from the category of pathogenic fungi. This study aims to isolate and characterize fungal pathogens in sweet corn leaves (Zea mays) of talenta varieties taken from agricultural land, Ketindan Agricultural Training Center, East Java. This research is an experimental study using Completely Randomized Design (CRD). The insulation method used direct plating and moist chamber. Characterization and identification based on macroscopic characters include: old colony shape, old colony color, old colony texture, young colony shape, young colony color, and young colony texture. Microscopic characters include hyphal wall, type of hyphae branching, presence or absence of septa, presence or absence of clamp connections, sporangium shape, sporangium color, spore shape, spore color. The results of the direct plating method obtained 5 species of pathogenic fungi, including: Helminthosporium sp., Rhizoctonia sp., Peronosclerospora spp., Puccinia sp., And Trichometaspheria sp., While the moist chamber method obtained 2 species of pathogenic fungi, namely: Helminthosporium sp. and Rhizoctonia sp.